Investigations on TaC Localized Dispersed X38CrMoV5-3 Surfaces with Regard to the Manufacturing of Wear Resistant Protruded Surface Textures - Spranger, Felix; Schirdewahn, Stephan; de Oliveira Lopes, Marcelo; Merklein, Marion; Hilgenberg, Kai (Lasers in Manufacturing and Materials Processing, 2019)
Purpose: The potential of lowered surface features as well as the application of wear resistant coatings have been known for many years to improve the tribological behavior of forming tools. More recent studies also discuss the capability of protruded microfeatures for adjusting the tribological behavior between contacting surfaces. The demand for a high wear resistance of such structures as well as their economical and reliable production, however, often limits the industrial application. The laser implantation process can overcome these limitations. In contrast to conventional cw-laser dispersing processes, where the formation of uniform metal matrix composite layers is intended, this surface engineering technique aims to improve the tribological behavior of contacting surfaces by a localized dispersing of pre-placed hard ceramic particles. This enables the formation of deterministic textures composed of separated wear resistant dome- or ring-shaped microstructures (implants). Since TaC shows very promising material properties for improving the wear resistance of tools exposed to severe operating conditions, this paper analyzes its suitability for pulsed laser implantation on X38CrMoV5-3 tool steel for the first time. Methods: In the experiments, the influence of the particles and the laser parameters (pulse power, pulse duration and focal diameter) on the material properties of the localized dispersed zones was studied by optical microscopy, scanning electron microscopy, energy dispersive X-ray spectroscopy and X-ray diffraction. The composite’s (micro-) hardness was measured and calculated by using a rule of mixture. Additionally, the influence of the laser parameters and the TaC particles on the geometrical properties of the implants was studied by optical microscopy and white light interferometry. Results: The results showed that defect-free implants with hardness values of 900 HV1 can be obtained at the focal spot, since a localized dispersing of the TaC particles is possible using a pulsed millisecond laser. However, in dependence of the laser intensity, also a partial dissolution of the initial particles occurs. This leads to the precipitation of new dendritic TaC nanoparticles and to varying contents of retained austenite in the matrix. Both effects have a strong influence on the implant hardness and must be considert by the rule of mixture. Regarding the geometrical response it was pointed out that protruded microfeatures with heights up to 10 μm can be created. In comparison to laser remelted zones, the implanted zones showed significantly altered weld pool profiles due to the influence of the particles on the melt convection. A transition of the implant shape from predominantly dome-shaped to predominantly ring-shaped was observed for intensities >1.7∙106 W/cm2 due to the onset of the keyhole effect. Conclusions: In conclusion, TaC particles seem to be very suitable for laser implantation on hot-work tool steels. The implants can be used for textures, where flat structures are needed. Since the TaC particles can be dispersed in the LIZ, it may be possible to reduce abrasive and adhesive wear due to the promising material properties of this hard phase and the improved hardness of the implants.
CRIS-Team Scopus Importer:2019-12-27
Keywords: Hot-work tool steel; Laser implantation; Localized laser dispersing; Surface texturing; TaC; Tantalum carbide; X38CrMoV5-3